Models and Algorithms of Time-Dependent Scheduling - Gawiejnowicz, Stanisław (Monographs in Theoretical Computer Science. An EATCS Series, 2020)
This book provides a comprehensive study of complexity results and optimal and suboptimal algorithms concerning time-dependent scheduling in single-, parallel- and dedicated-machine environments. This is the first monograph on time-dependent scheduling.